2011
DOI: 10.1007/s10067-011-1698-1
|View full text |Cite
|
Sign up to set email alerts
|

Anti-C1q antibodies are associated with systemic lupus erythematosus disease activity and lupus nephritis in northeast of China

Abstract: This study aimed to investigate the associations of anti-C1q antibodies with systemic lupus erythematosus (SLE) disease activity and lupus nephritis (LN) in northeast of China. Ninety patients with SLE, 37 patients with other autoimmune diseases, and 40 healthy donors in northeast of China were enrolled. Serum anti-C1q antibodies were measured by ELISA with 20 RU/ml as the threshold of positive results. The prevalence and levels of anti-C1q antibodies in SLE group (50%, 20.54 ± 34.67 RU/ml) were significantly … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
10
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 19 publications
4
10
0
Order By: Relevance
“…Braun et al found a prevalence of 61.7% in biopsy proven lupus nephritis cases 29 and Wener et al, 48% 21 . The strongest clinical association we observed for anti-C1q was with proteinuria, consistent with published data 12, 14, 16, 27, 34 . Our study was undertaken in patients with SLE from a multicenter, multiethnic patient population and an equal number of patients with other rheumatic diseases (controls), in which complete clinical, serologic and candidate criteria variables were assessed for the purpose of deriving SLE classification rules.…”
Section: Discussionsupporting
confidence: 92%
“…Braun et al found a prevalence of 61.7% in biopsy proven lupus nephritis cases 29 and Wener et al, 48% 21 . The strongest clinical association we observed for anti-C1q was with proteinuria, consistent with published data 12, 14, 16, 27, 34 . Our study was undertaken in patients with SLE from a multicenter, multiethnic patient population and an equal number of patients with other rheumatic diseases (controls), in which complete clinical, serologic and candidate criteria variables were assessed for the purpose of deriving SLE classification rules.…”
Section: Discussionsupporting
confidence: 92%
“…[172127] Our study showed a slightly higher incidence of anti-C1q antibodies (60%) in LN patients compared to non-LN patients (53.3%). This finding was similar to the studies reported by Zang et al .…”
Section: Discussionmentioning
confidence: 71%
“…and Katsumata et al . [2122] It was suggested that the circulating anti-C1q antibodies may bind to the C1q deposits in the kidneys of LN patients and this consumption of serum anti-C1q antibodies by binding to C1q-containing immune complexes could be responsible for the lack of significant difference among LN and non-LN patients. [24] It was also reported that although a high prevalence of anti-C1q antibodies correlated with proliferative LN, the predictive value of 27-68%, in the presence of anti-C1q antibodies, among LN patients was too low to reliably identify them as LN, and that up to 46% renal flares occurred in patients who did not develop anti-C1q antibodies.…”
Section: Discussionmentioning
confidence: 99%
“…Anti-C1q antibodies are highly prevalent in prototypical autoimmune disease, systemic lupus erythematosus (SLE), exhibiting strong correlation with lupus nephritis (Hu et al, 2013;Mahler et al, 2013;Trouw et al, 2004;Zhang et al, 2011). These antibodies are also detected in hypocomplementemic urticarial vasculitis, rheumatoid vasculitis, IgA nephropathy, anti-glomerular basement membrane (anti-GBM) nephropathy, and HIV infection (Mahler et al, 2013).…”
Section: Introductionmentioning
confidence: 97%